DIRECTIONS OF PREPARATION OF FUTURE TEACHERS TO THE USE OF DISTANCE LEARNING TECHNOLOGIES IN PROFESSIONAL ACTIVITY (PRAXIOLOGICAL ASPECT OF THE ACTIVITY APPROACH) - Tatyana A. Boronenko; Vera S. Fedotova (Obrazovanie i Nauka)
The aim of the article is to demonstrate the need of preparing future teachers to use distance learning technologies in the professional activities. Introduction in educational process of distance learning technologies contributes to improving the quality of education. Methods. The authors’ technique of preparation of students of pedagogical specialities to work in the information-educational environment is designed on the basis of the analysis and generalisation of numerous scientific publications. Results. The system of training to implementation of the distance learning technologies in the teaching activity is developed and described, consisting of the following directions: realisation within the program of the principal educational program of specialised training courses in variable-based curriculum parts; the organisation of educational and research activity of students with the use of distance learning technologies; classroom-based and extracurricular independent work of students directed to designing of teaching and learning aids and materials on the basis of distance learning technologies; application of elements of distance learning technologies for students’ teaching; attraction of students to formation of corpus of multimedia educational resources of university. The purposes, the content and expected results of each direction are specified. Scientific novelty. The authors point out that concrete scientifically wellfounded methodical recommendations for the future teachers on implementation of distance learning technologies haven’t been presented in the Russian literature till now; despite an abundance of scientifically-information sources of distance learning technologies and sufficiently high-leveled degree knowledge of the issues of its efficiency in educational activity, conditions of introduction of such technologies in high school, construction of models of distance training. Authors of article have tried to close this gap. Practical significance. The authors of the presented study propose and describe task-oriented, stage-by-stage, consistent preparation of the future teachers for an effective usage of distance learning technologies. Such preparation allows teachers to rationalize teaching and training processes, to improve means of monitoring, diagnostics of educational activity; it considerably expands didactic, information, methodical and technological possibilities of pedagogical activity.